2007
DOI: 10.1088/0026-1394/45/1/007
|View full text |Cite
|
Sign up to set email alerts
|

The use of diaphragm bellows to construct a constant pressure gas flowmeter for the flow rate range 10−7 Pa m3 s−1to 10−1 Pa m3 s−1

Abstract: A constant pressure gas flowmeter using a directly driven diaphragm bellows as a volume displacer was studied. This flowmeter is perfectly vacuum-sealed, does not contain elastomers and liquids that would prevent outgassing at elevated temperatures and can achieve a smaller ratio of the final volume to the displaced volume than when bellows are used, so that the uncertainty in generating small flow rates can be small. As, when a bellows is used in the volume displacer, the displaced volume cannot be calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Computer control also ensures maintenance of all the necessary pauses for stabilization of the system. (2) No surface freshly exposed to the surrounding atmosphere may be immersed in the chamber during the measurement of the entire dependence (i.e. one curve for a given P D value).…”
Section: Error In the Methods Caused By Outgassing From The Walls Of Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer control also ensures maintenance of all the necessary pauses for stabilization of the system. (2) No surface freshly exposed to the surrounding atmosphere may be immersed in the chamber during the measurement of the entire dependence (i.e. one curve for a given P D value).…”
Section: Error In the Methods Caused By Outgassing From The Walls Of Tmentioning
confidence: 99%
“…Constructions of constant-pressure gas flowmeter employing directly driven bellows and/or diaphragm bellows as volume displacers were described in recent decades [1,2]. Practical advantages of this solution are obvious: difficulties with a dynamic seal [3,4] or with liquid [5] can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Jousten [15] s Calibrated bellows 12 5 Â 10 À 7 13 0.2 Jousten [16] s Calibrated bellows 12 5 Â 10 À 7 13 0.14 Calcatelli [17] s Pistonþ cylinderþ custom PTFE seal 5, 20 1 Â 10 À 5 0.7 0.2 Berg [18] s/r Pistonþ bellows þ oil-filled cylinder 102 1 Â 10 À 1 270 0.02 Cignolo [19] s/r Pistonþ lubricated o-ring 120 9 Â 10 À 2 1900 0.01 Kramer [20] s/r Double piston 16 1 Â 10 À 3 1.3 0.03 Cheng [21] s Pistonþ bellows þ oil-filled cylinder ? 5 Â 10 À 6 0.05 0.57 Gronych [22] s Calibrated bellows 9,30 3 Â 10 À 4 55 1. This work s/r Pistonþ FEP encapsulated o-ring 25 1 Â 10 À 2 100 0.03 [23]).…”
Section: Reference S/r Typementioning
confidence: 99%
“…The third type of flow standard, calibrated bellows [12,15,16,22], also has no sliding seal, and it eliminates the complications due to the oil by driving the bellows directly. Its chief disadvantage is that the bellows volume V(x) must be calibrated as a function of its linear displacement x. Jousten et al [12] found that V(x) was more linear for a formed bellows than for a welded diaphragm bellows, although Gronych et al [22] later were able to use a welded diaphragm bellows despite its nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation